The transferential relationship in family courts: A psychoanalytic perspective (Research, Society and Development, 2024)
This article aims to analyze the transference relationship in Family Courts, highlighting the role of the psychoanalyst in this scenario. Part of the legal processes that arrives at the Family Courts expects the psychologist that is guided by psychoanalysis who occupies this position to carry out a study that will also serve as a mediator of the problems arising from the divorce. Clinical listening allows to the parts that are involved in the legal process to express their anxieties; as long as transference is used as an ethical device that promotes the construction of knowledge and at the same time places responsibility on the person for their position in the separation. Managing this transfer is trying to intervene so that the subject comes below or beyond the legal process supported by the demand to the judiciary. This is a theoretical study that used the literature review methodology to guide this discussion. It is concluded that when exercising the role of judicial expert, the psychoanalyst, supported by his ethics, is guided to bring out the speeches of the people involved so that he can discern what their demand is, and produce a study within his field with the purpose of offering support for the legal decision.